The Relationship between Assault and Physical Health Complaints in a Sample of Female Drinkers: Roles of Avoidant Coping and Alcohol Use - Bedard-Gilligan, Michele (2013)
Trauma exposure and PTSD are associated with poorer physical health. Psychological and behavioral mechanisms may help account for this relationship. In this study, we tested avoidant coping and alcohol use as mediators of the relationship between trauma exposure, PTSD, and self-reported physical health complaints in female drinkers. In 827 college women, we compared three groups: women with no trauma history, women with a sexual assault but no PTSD, and women with a sexual assault and PTSD, on avoidant coping, alcohol use, and physical health complaints. We found that PTSD was positively associated with alcohol use and that both PTSD and trauma exposure were associated with increased avoidant coping. We also found that avoidant coping mediated the relationship between trauma, PTSD and physical health complaints. Alcohol use did not predict physical health but was associated with PTSD. These results suggest that in female college students coping may be more critical in the PTSD/physical health relationship than alcohol and have implications for targeting coping in young trauma-exposed women to improve physical health.